Reduksi Semen Menggunakan Silicafume Dengan Bahan Tambah Naphthalene Terhadap Kuat Tekan Dan Kuat Lentur Beton - Lido, Kurniawan; Setiawan, Arman; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Concrete is a very popular construction material and is widely used throughout the world. This is because concrete has several advantages, such as high strength, weather resistance, and relatively low cost, but forces the rate of cement production to increase which can cause carbon emissions and air pollution. Therefore, using silica fume as an alternative material as a cement reduction material by adding additional materials to strengthen the concrete mixture such as naphthalene. In this study, a normal concrete compressive strength design of 25 MPa was used with the aim of the study to obtain the effect of Cement Reduction Using Silica fume with Naphthalene Additives on the Compressive Strength and Flexural Strength of Concrete. The mixing method is carried out by partially replacing cement with silica fume by 10% and adding naphthalene additives of 0.2%, 0.4%, 0.6%, 0.8%, and 1%, respectively, by conducting concrete compressive and flexural strength tests. This study shows that the addition of Silica Fume as a partial replacement of cement by 10% with the addition of Naphthalene increases the compressive strength of concrete, and for a variation of 1% it gets the largest compressive strength value of 26.82 Mpa, and also increases the flexural strength value of concrete, and for a variation of 1% it gets the largest compressive strength value of 5.33 Mpa.